2022
DOI: 10.1111/eea.13188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host plants on development and reproduction of Diaphorina citri and their host preference

Abstract: The effects of five host plant species – tangerine, Citrus reticulata Blanco cv. Shatangju, C. reticulata cv. Ponkan, orange jasmine, Murraya paniculata (L.) Jack, lemon, Citrus limon (L.) Osbeck, and navel orange, Citrus sinensis (L.) Osbeck (all Rutaceae) – on the life‐table parameters and host preference of the citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), were evaluated under laboratory conditions. In the presence of the host plants tested, citrus psyllid showed higher preference for nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Enterococcaceae dominated in the Shatangju-, navel orange-, and lemon-feeding populations and was significantly higher in the Shatangju-feeding population. Interestingly, our previous studies on the effects of host plants on D. citri development and reproduction confirmed that Shatangju was the most appropriate host for D. citri [ 39 ]. We can hypothesize that Enterobacteriaceae play an important role in the fitness of D. citri .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Enterococcaceae dominated in the Shatangju-, navel orange-, and lemon-feeding populations and was significantly higher in the Shatangju-feeding population. Interestingly, our previous studies on the effects of host plants on D. citri development and reproduction confirmed that Shatangju was the most appropriate host for D. citri [ 39 ]. We can hypothesize that Enterobacteriaceae play an important role in the fitness of D. citri .…”
Section: Discussionmentioning
confidence: 76%
“…The microbial diversity in the Shatangju-feeding population was the lowest, suggesting Shatangju provides different nutrients for the growth and development of D. citri . Our previous research has shown that D. citri feeding on Shatangju produces more eggs than when they feed on the other four species [ 39 ]. On Ponkan, the high diversity in the GM community may contribute to the absorption of specific nutrients from unbalanced feeding and to the adaptation of D. citri to the feeding environment [ 29 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its presence in only three residential sites in the south suggests that its spread may be currently limited in the country. Surprisingly, the ACP was detected feeding on three of the most suitable host plants 47 , 48 in the coastal part of the country with altitude less than 20 m above sea level (Table 1 ). It is well established that higher altitude limits the incidence of the ACP with its population levels decreasing at higher altitudes probably as a result of differential temperature, air pressure, oxygen level, ultraviolet light or their combinations 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera: Liviidae), is one of the most serious citrus pests worldwide due to its role as a vector of the uncultured proteobacterium Candidatus Liberibacter asiaticus ( C Las) that causes Huanglongbing (HLB) [ 1 , 2 ]. As a phytophagous pest, D. citri feeds on the phloem sap of plants and has a narrow host range in the family Rutaceae, such as the commercial citrus species Citrus limon , C. sinensis , C. aurantium , C. paradisi , C. aurantifolia , C. maxima , and C. reticulata Blanco, as well as other economic plants Clausena lansium and Murraya exotica [ 3 – 5 ]. The performance of D. citri feeding on different host plants was different.…”
Section: Introductionmentioning
confidence: 99%
“…Shatangju, C. reticulata cv. Ponkan, M. exotica , C. limon , and C. sinensis have been evaluated [ 5 ]. Furthermore, the different fitness of D. citri fed on C. sinensis and M. exotica was also investigated [ 7 ].…”
Section: Introductionmentioning
confidence: 99%